2014
DOI: 10.3748/wjg.v20.i42.15703
|View full text |Cite
|
Sign up to set email alerts
|

Chunggan extract, a traditional herbal formula, ameliorated alcohol-induced hepatic injury in rat model

Abstract: The present study evidenced that CGX has hepatoprotective properties via modulation of fibrogenic cytokines and alcohol metabolism in alcoholic liver injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 46 publications
0
13
0
Order By: Relevance
“…miltiorrhiza . We previously compared the antihepatofibrotic activities of thirteen herbs of CGX with respect to TGF- β inhibition using the HSC T-6 cell line [ 45 , 46 ]. From those experimental data and practical theory of the traditional Korean pharmacology, we finally selected the abovementioned three herbal plants.…”
Section: Discussionmentioning
confidence: 99%
“…miltiorrhiza . We previously compared the antihepatofibrotic activities of thirteen herbs of CGX with respect to TGF- β inhibition using the HSC T-6 cell line [ 45 , 46 ]. From those experimental data and practical theory of the traditional Korean pharmacology, we finally selected the abovementioned three herbal plants.…”
Section: Discussionmentioning
confidence: 99%
“…It comprises herbal drugs which originated from TKM prescription. It has been proven to improve various chronic liver disease such as cholestatic liver fibrosis, liver chrrhosis, alcoholic liver disease, and chronic viral hepatitis in many patients or rat model [24][25][26] .…”
Section: Discussionmentioning
confidence: 99%
“…Chunggan extract (CGX) is a commercially marketed herbal medicine of 13 herbs, which finds its utility as a potent "liver cleaning" agent (Choi et al, 2006;Kim et al, 2014). Kim et al (2014) observed pharmacological properties of CGX with the main focus on molecules related to alcohol metabolism and profibrogenic cytokines. They also saw the mechanism in ratderived HSC cell line (using HSC-T6 cells) (Kim et al, 2014).…”
Section: Ethnopharmacological Applications Targeting Alcohol Abusementioning
confidence: 99%
“…Kim et al (2014) observed pharmacological properties of CGX with the main focus on molecules related to alcohol metabolism and profibrogenic cytokines. They also saw the mechanism in ratderived HSC cell line (using HSC-T6 cells) (Kim et al, 2014).…”
Section: Ethnopharmacological Applications Targeting Alcohol Abusementioning
confidence: 99%
See 1 more Smart Citation